A randomized, controlled multicentric study of inhaled budesonide and intravenous methylprednisolone in the treatment on acute exacerbation of chronic obstructive pulmonary disease. (December 2016) - Ding, Zhen; Li, Xiu; Lu, Youjin; Rong, Guangsheng; Yang, Ruiqing; Zhang, Ruixia; Wang, Guiqin; Wei, Xiqiang; Ye, Yongqing; Qian, Zhaoxia; Liu, Hongyan; Zhu, Daifeng; et al.
Abstract: Background: Almost all international guidelines recommend corticosteroids for management of exacerbations of chronic obstructive pulmonary disease (COPD), because it leads to improved outcomes of acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Nevertheless, due to its side effects, there are still concerns regarding the use of systemic corticosteroid (SC). Inhaled corticosteroids (IC) can be used as an alternative to SC, while reducing the risk of occurrence of side effects. Purpose: To measure the clinical efficacy and side effects of nebulized budesonide and systemic methylprednisolone in AECOPD. Methods: Valid data from 410 AECOPD patients in 10 hospitals was collected. Patients were randomly divided into 2 groups; budesonide group, treated with nebulized budesonide (2 mg 3 times/day); and methylprednisolone group, treated with intravenously injected methylprednisolone (40 mg/day). COPD assessment test (CAT), arterial blood gas analysis, hospitalization days, adverse effects, fasting blood glucose, serum creatinine, alanine aminotransferase levels, and blood drug were measured and analyzed in both groups. Results: Symptoms, pulmonary function and arterial blood gas analysis were significantly improved after treatment in both groups ( P < 0.05), with no significant differences between them ( P > 0.05), while incidence of adverse events in the budesonide group was lower ( P < 0.05). No significant differences in CAT score, days of admission, blood gas analysis results and physiological and biochemical indexes were found between the two groups. Patients treated with methylprednisolone showed a higher degree of PaO2 level improvement. Conclusion: Results show that inhalation of budesonide (2 mg 3 times/day) and systemic methylprednisolone (40 mg/day) had similar clinical outcome in AECOPD. In conclusion, inhaled budesonide is an alternative to systemic corticosteroids in AECOPD treatment. Highlights: A multicentric, randomized controlled trials of inhaled budesonide in AECOPD. Inhaled budesonide resulted in similar efficacies as systematic methylprednisolone. Inhalation of budesonide could be an alternative treatment of AECOPD.